PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) PADA PERANCANGAN OVEN MULTIFUNGSI UNTUK PENGERINGAN DAN PENGASAPAN IKAN - Sujana, Ivan; Imansyah, Fitri; Djanggu, Noveicalistus H.; Anggela, Pepy (Fakultas Teknik UM Pontianak, 2024)
The large potential of marine fisheries in Tanjung Saleh Village, Kubu Raya Regency has not been followed by an increase in the standard of living and welfare of local fishermen. Processing of caught fish still uses traditional methods, there is no touch of technology to increase capacity in processing fish production. So that further research is needed regarding the production of science and technology in the design of multifunctional fish processing equipment that can be used for the drying process of fish and the process of smoking fish. The tool design process uses the QFD method where the HOQ will identify the fishermen's desires which are then translated into technical responses in the manufacture of multifunctional fish processing tools. The results of the HOQ obtained that the attributes desired by fishermen are the criteria for tools that are easy to operate, smoke circulation, drying temperature, tool hygiene, safe combustion smoke, and strong and sturdy tools. Based on the value of the repair ratio that has the largest value is the attribute of smoke resulting from burning wood/shells, which is safe for workers.